A Posterior Approach to Open Reduction and Internal Fixation of Displaced Posterior Cruciate Ligament Tibial Osseous Avulsions. Issue 1 (January 2018) - Hooper, Perry O.; Bevan, Patrick J.; Silko, Christopher; Farrow, Lutul D.
Abstract : Background: The true prevalence of displaced tibial-sided avulsion injuries of the posterior cruciate ligament (PCL;Video 1 ) is unknown, and the majority of data regarding management has been published in areas other than the Western world, such as China and India (perhaps due to the higher prevalence of two-wheeler motorcycle accidents in these areas). Despite the rarity of data, a better understanding of the approach, fixation techniques, and outcomes is necessary to provide quality patient care. These injuries generally require surgical intervention as nonoperative management leads to complications—specifically, knee arthrofibrosis1, 2 . There is no consensus regarding the optimal surgical approach for these injuries. A recent systematic review demonstrated that both open and arthroscopic surgical treatment provide satisfactory complication rates and outcomes in the majority of cases3 . However, the arthroscopic approach can be performed by only a highly skilled arthroscopist; thus, in this article we focus on the open approach to reach a broader audience of capable surgeons. Description: The principal steps for open reduction and internal fixation of the tibial avulsion fracture include the following: Place the patient in a prone position and utilize a curvilinear L-shaped incision with the longitudinal portion over the medial head of the gastrocnemius muscle and the transverse portion starting distal to the joint line and extending laterally past the midline. Develop the interval between the semimembranosus and medial gastrocnemius muscles, as originally described by Burks and Schaffer4 . Lateral retraction of the gastrocnemius muscle exposes the posterior aspect of the capsule, allowing for a vertical capsular incision to adequately visualize the avulsed osseous fragment. Prepare the osseous bed and remove hematoma and/or debris. Reduce the avulsed fragment and obtain provisional fixation with Kirschner wires. Confirm reduction under fluoroscopy with emphasis on sagittal plane alignment. Obtain definitive fixation with the method dictated by the fracture orientation. Options include screw(s) with or without a washer, sutures, Kirschner wires, staples, and toothed plates2, 5 -7 . Alternatives: An arthroscopic approach can be performed, with results that are similar to those of an open procedure, but considerable expertise is required to perform this procedure arthroscopically. Nonsurgical management is not recommended as it frequently leads to loss of knee motion. Rationale: The exact operative indications for PCL injuries remain in question, but we believe that displaced tibial avulsion injuries at the PCL attachment always require operative treatment.